Towards Automated Decision-Making at Court: The Use of Artificial Intelligence for Drafting and Rendering Court Decisions - Stolper, Inesa (Teisė, 2024)
The integration of Artificial Intelligence (AI) into the judicial system presents both opportunities and challenges. AI can expedite proceedings, reduce costs, and broaden access to justice by serving as a decision-making assistant or an autonomous decision-maker. The article is structured into three main parts: an overview of AI technologies and their classification, a detailed examination of AI‘s role as an assistant in judicial decision-making, and a consideration of AI as an autonomous decision-maker. The analysis revealed that while AI can significantly assist in legal proceedings by offering preliminary judgments or legal advice, its capacity as an autonomous decision-maker is complex. A robust legal foundation respecting procedural norms and Article 6 of the European Convention on Human Rights (ECHR) is crucial. This legal framework should define AI‘s operational boundaries within the judiciary to prevent infringement on the right to a fair trial. Moreover, in line with Article 22 of the General Data Protection Regulation (GDPR), there must be opportunities for human intervention and the ability to contest AI-generated decisions, safeguarding a human-centric approach to justice. The issue of bias in AI, reflecting pre-existing prejudices in training data, underscores the importance of careful programming, dataset selection, and ongoing oversight to avoid perpetuating discriminatory practices. AI‘s potential in simulating legal reasoning in straightforward cases suggests a cautious yet optimistic engagement with technology, advocating for its selective application in scenarios where public hearings are unnecessary. The paper concludes that while AI presents a promising tool for enhancing judicial processes, its use must be approached with caution. It advocates for a balanced, multi-faceted approach to AI integration, emphasizing ongoing evaluation, legal regulation, and the selective application of AI technologies.